Antibacterial Potential of Anacardium Occidentale Juice against Clinical Isolates of Streptococcus Mutans -An In Vitro Study - Krisna Malay, Kausalyah; R.V, Geetha; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The aim of the present study was to evaluate the antibacterial activity of Anacardiumoccidentale juice on Streptococcus mutans, the potent initiator and leading cause of dental caries worldwide. Background: Tooth decay is a common problem that occurs when acids in the mouth dissolves the outer layers of the teeth. It is also known as dental decay or dental caries. Traditional system such as Homeopathy, Siddha, and Ayurveda uses plant-based medicine to treat varies diseases caused by bacteria and other organisms. Anacardimoccidentalecommonly known as cashew apple possesses high nutritive values because it contains high value of Vitamin C and minerals such as, phosphorus, iron and calcium. The cashew apple shows to have several bioactivities such as antimicrobial, antioxidant, antimutagenic. Materials and Methods: Antibacterial activity of this juice was screened against Streptococcus mutans, using disc diffusion technique. The extract of Anacardiumoccidetale were loaded on sterile filter paper discs measuring 6mm diameter in the following concentrations 50µl, 100µl and 200 µl respectively. The discs were dried and kept aseptically, then is placed in the agar plates. The plates were incubated at 37°C overnight and the zone of inhibition of growth was measured in millimeters. All the tests were done in triplicate to minimize the test error. Results: The results of this study showed that the extracts exhibited antibacterial activity against the bacterial species tested. The extract of Anacardiumoccidentale was effective against Streptococcus mutans with a zone of inhibition of 20mm diameter (at conc200 µl.). The control (chlorhexidine) showed a zone of 29mm diameter. Dental caries is a microbial disease that results in the destruction of mineralized tissue of the teeth. Streptococcus mutans is the potent initiator and leading cause of dental caries worldwide . It is considered to be the most cariogenic of all of the oral Streptococci.Conclusion: The traditional claim of Anacardiumoccidentaleas an antimicrobial have been confirmed as the extract of it showed an activity against the microorganism used in the study, the Streptococcus mutans